Bài $ 3 $. $ a $. ( $ 6 $ $\frac{4}{9}$ $ + $ $\frac{7}{11}$ ) $ – $ ( $ 4 $ $\frac{4}{9}$ $ – $ $ 2 $ $\frac{4}{11}$ )

Question

Bài $ 3 $.
$ a $. ( $ 6 $ $\frac{4}{9}$ $ + $ $\frac{7}{11}$ ) $ – $ ( $ 4 $ $\frac{4}{9}$ $ – $ $ 2 $ $\frac{4}{11}$ )

in progress 0
Arianna 1 tháng 2021-11-04T04:29:20+00:00 2 Answers 3 views 0

Answers ( )

    0
    2021-11-04T04:31:00+00:00

    Đáp án:

     

    Giải thích các bước giải:( 6 4/9+ 7/11) – (4 4/9- 2 4/11)

                                                = 6 4/9+ 7/11 – 4 4/9- 2 4/11

                                                  =( 6 4/9- 4 4/9)+ ( 7/11- 2 4/11)

                                                  = 2+ (-2) 3/11

                                                   = -1 8/11

    Bạn có thể kiểm tra lại. Chúc bạn thành công

     

    0
    2021-11-04T04:31:19+00:00

    = 6$\frac{4}{9}$ + $\frac{7}{11}$ – 4$\frac{4}{9}$ – 2$\frac{4}{11}$ $\frac{4}{11}$ $\frac{4}{11}$ 

    =(6$\frac{4}{9}$ – 4$\frac{4}{9}$)+($\frac{7}{11}$ – 2$\frac{4}{11}$ )

    =2+(-2)$\frac{3}{11}$ 

    =1$\frac{8}{11}$ 

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )